UBV Monitoring of EPS Aurigae (I) - Il-Seong Nha; Yong-Sam Lee; Ho-Il Kim; Kyoung-Hee Lee (Journal of Astronomy and Space Sciences, 1988)
UBV photometric monitoring of Eps Aurigae has been made at Yonsei University Observatory since the 1982-1984 eclipse. Among observations made in four seasons (1984-5, 1985-6, 1986-7, 1987-8) after the 1982-84 eclipse ended the observations of the latest season are presented. Standardized UBV light curves of Eps Aur exhibit a light variation in a semi-regular fashion with the amplitudes of 0.12, 0.19, and 0.29 for V, B, and U, respectively. Durations of this light variation may show a color dependency with the mean vale of about 78 days whose minimum light on near JD2447118.